Bioactivities of extracts from Eichhornia crassipes (Mart.) Solms. against the larvae of diamondback moth, Plutella xylostella L - CAI Xia; SHI Zu-hua; SHI Ying-li (浙江大学学报. 农业与生命科学版)
The effects of ethanol extracts from Eichhornia crassipes on the larvae of diamondback moth Plutella xylostella were investigated in laboratory by measuring antifeeding action of the extracts, body weight gains of the larvae and larval mortality after the larvae had fed on the extracts-coated cabbage leaves. The results indicated that leaf consumption by the insects and body weight gain of the larvae were reduced, and the larval mortality was increased. The higher the concentration of the extracts was, the more severe the effects on the pest were. The results showed that the medium antifeedant concentrations (AFC50) of the extract in case of 3rd instar P. xylostella larvae were 66.09 g/L and 293.35 g/L for conditions of choice and no-choice tests, respectively.